Altered default mode network functional connectivity in individuals with co-occurrence of schizotypy and obsessive-compulsive traits. (30th November 2020) - Wang, Yong-ming; Cai, Xin-lu; Zhou, Han-yu; Zhang, Rui-ting; Zhang, Yi-jing; Wang, Yan-yu; Cheung, Eric F.C.; Chan, Raymond C.K.
Highlights: we examined the differences in resting-state functional connectivity between sub-regions of the Default Mode Network (DMN) and whole brain in individuals with high schizo-obsessive traits (SOT), high schizotypal traits (SCT) alone, high obsessive-compulsive traits (OCT) alone and low trait scores (LT). We found that the SOT group showed the most reduced functional connectivity within the DMN compared with the other groups, the SOT group also showed increased connectivity between the DMN and the Salience Network, and between the DMN and the Auditory Network compared with the LT group. These findings highlight different changes in DMN-related functional connectivity associated with high SOT, SCT and OCT traits and may provide insight into the dysfunctional brain networks in the early stage of schizophrenia spectrum disorders. Abstract: In this study, we examined differences in resting-state functional connectivity between sub-regions of the Default Mode Network (DMN) and whole brain voxels in 22 individuals with high schizo-obsessive traits (SOT), 30 with high schizotypal traits (SCT) alone, 20 with high obsessive-compulsive traits (OCT) alone and 30 with low trait scores (LT). We found that the SOT group showed the most reduced functional connectivity within the DMN compared with the other groups. The SOT group also showed increased connectivity between the DMN and the Salience Network, and between the DMN and the Auditory Network compared with the LT group. The SCT group exhibited increased connectivity between the DMN and the Salience Network, and between the DMN and the Executive Control Network (ECN) compared with the LT group. The OCT group exhibited decreased connectivity within the DMN, between the DMN and the Salience Network, and between the DMN and the ECN compared with the LT group. These findings highlight different changes in DMN-related functional connectivity associated with high SOT, SCT and OCT traits and may provide insight into the dysfunctional brain networks in the early stage of schizophrenia spectrum disorders.